There are no broad subjects in Standard Arabic - Alqarni Muteb; Alanazi Mohammad (Linguistics)
The current article argues that the multiple nominative constructions of the Japanese type do not exist in Standard Arabic. Based on evidence from binding, A′-interception and Case, the article shows that the so-called ‘broad subject’ is a clitic left-dislocated element base generated in the A′-domain. The article thus follows the spirit of the analysis proposed by Landau (e.g., Landau, Idan. 2009. Against broad subjects in Hebrew. Lingua 119(1). 89–101), who denies the existence of broad subjects in Hebrew, concluding that broad subjects do not exist in Semitic languages at all.